Error Analysis in Spoken and Writen Language - Zulkifli; Risnawati (Politeknik Negeri Sriwijaya, 2026)
ABSTRACT: Error Analysis (EA) is an important branch of applied linguistics that examines the occurrence, nature, causes, and consequences of errors in language learning and use. This paper discusses the concept of error analysis in both spoken and written language, emphasizing its role in understanding the language acquisition process. Drawing on the theories of Corder and other scholars, the study highlights the distinction between errors, mistakes, slips, and solecisms, as well as the significance of learner errors as indicators of linguistic development and transitional competence. The paper reviews various classifications of language errors, including substance errors, text errors, semantic errors, grammatical errors, morphological errors, and syntactic errors. Particular attention is given to common errors in writing, such as misspellings, punctuation mistakes, typographical errors, dyslexic errors, and confusibles, as well as pronunciation and suprasegmental errors in spoken language. Furthermore, the study explores lexical-semantic errors, including confusion of sense relations and collocational errors, together with grammatical deviations at the morphological and syntactic levels. The findings suggest that language errors are a natural and inevitable part of the learning process rather than signs of failure. Error analysis provides valuable insights for researchers in understanding language acquisition, assists teachers in identifying learners’ difficulties and improving instructional strategies, and helps learners recognize and correct their linguistic weaknesses. Consequently, errors should be viewed positively as evidence of progress and development in language learning. The study concludes that systematic analysis of spoken and written language errors contributes significantly to more effective language teaching and learning practices. Keywords: Error Analysis, Spoken Language, Written Language, Language Learning, Linguistic Errors, Applied Linguistics